FINANCIAL REPORT ANALYSIS OF THE JENEPONTO REGENCY REGIONAL GOVERNMENT FOR 2021 - Wisnu Sri Baroto (Transpublika Publisher, 2022)
Financial reports are organized reports that detail a reporting entity's financial situation and transactions. The purpose of financial reports is to provide users with valuable information about the financial condition, budget execution, cash flows, and financial performance of a reporting business in order for them to make and evaluate resource allocation decisions. Consequently, local government financial reports (LKPD) are financial reports prepared by a local government (PPKD by merging financial reports issued by each SKPD), which is a form of local government accountability to the public about the management of state finances. Specifically, the objective of local government financial reports is to provide valuable information for decision making and to establish the reporting entity's accountability for the entrusted resources. Regional Government Financial Reports are analyzed for Regional Government Financial Reports (LKPD). This analysis can be used to help users of financial statements in terms of how to understand financial reports, interpret numbers in financial reports, evaluate financial reports and use financial information for decision making. With the analysis of these financial statements, users of financial reports will obtain information regarding regional financial accountability, regional wealth, and local government financial performance. This study uses descriptive research methods with a qualitative approach and literature analysis or literature study as a data collection technique. This financial report analysis focuses on financial reports that utilize an analytical technique to identify and understand existing issues and opportunities so that they will be very useful in making a decision.